2014
DOI: 10.1016/j.ultsonch.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of phenolics from wine lees: Modeling, optimization and stability of extracts during storage

Abstract: The ultrasound-assisted extraction process of phenolics including anthocyanins from wine lees was modeled and optimized in this research. An ultrasound bath system with the frequency of 40 kHz was used and the acoustic energy density during extraction was identified to 48 W/L. The effects of extraction time, extraction temperature, solvent-to-solid ratio and the solvent composition on the extraction yields of total phenolics and total anthocyanins were taken into account. The extraction process was simulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(107 citation statements)
references
References 44 publications
7
98
1
1
Order By: Relevance
“…The first is called the "washing" step, which covers the first 10-20 min of extraction. In this step the dissolution of the soluble components on the surfaces of the matrix is carried out and it is at this stage that up to 90% of the recovery of the total content of the phenolic compounds can be achieved thus indicating a considerably rapid extraction rate [45]. In the second stage, known as "slow extraction", the mass transfer of the solute from the matrix into the solvent is carried out by diffusion; the time of this process can last from 60 to 100 min [37].…”
Section: Extraction Timementioning
confidence: 99%
“…The first is called the "washing" step, which covers the first 10-20 min of extraction. In this step the dissolution of the soluble components on the surfaces of the matrix is carried out and it is at this stage that up to 90% of the recovery of the total content of the phenolic compounds can be achieved thus indicating a considerably rapid extraction rate [45]. In the second stage, known as "slow extraction", the mass transfer of the solute from the matrix into the solvent is carried out by diffusion; the time of this process can last from 60 to 100 min [37].…”
Section: Extraction Timementioning
confidence: 99%
“…However, when higher temperature was applied in extraction, extraction yield and curcumin content in extract may decrease because temperature might be continue to increase by the high intensity of ultrasound. Also, the oxidation of some compounds may occur due to the small amount of moisture content in material [21,22]. Moreover, increasing temperature increased the volatility and diffusion of the solute and reduced the density of CO2.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Several studies have reported that extracts of perilla leaves have high antioxidant capacity, mostly due to the presence of polyphenolic compounds (Lee et al, 2013;Zhou et al, 2014). Phenolic compounds are well-known for their beneficial health properties, attributed to their antioxidant and antiradical activities (Tao et al, 2014;Krishnaswamy et al, 2013;Heim et al, 2002). Moreover, rosmarinic acid (RA) has been shown to be the main biologically active polyphenolic compound in perilla leaves (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of these methods, ultrasound-assisted extraction (UAE) technology has gained increasing popularity due to its advantageous properties, including high extraction efficiency, good reproducibility, low solvent consumption, speed, low cost, environmental friendliness and easy scale up for industrial applications (Tao et al, 2014;Cravotto et al, 2008;Vinatoru, 2001;Vuong et al, 2014). The enhancement of extraction using ultrasound is mainly attributed to acoustic cavitations produced in the solvent (Ma et al, 2008;Velickovic et al, 2008), and ultrasound technology has been used to improve different food processes (Kiani & Sun, 2011;Kiani et al, 2012) in addition to extraction.…”
Section: Introductionmentioning
confidence: 99%